Identification of leukemic and pre-leukemic stem cells by clonal tracking from single-cell transcriptomics - Lars Velten (Nature Portfolio, 2021)
Leukaemic stem cells drive acute myeloid leukaemia (AML) progression and relapse but they are incompletely characterized. Here, the authors combine single-cell transcriptomics and clonal tracking using nuclear and mitochondrial somatic variants to distinguish healthy, pre-leukaemic and leukaemic stem cells in AML.